2013
DOI: 10.1111/jog.12229
|View full text |Cite
|
Sign up to set email alerts
|

Role of subcutaneous closure in preventing wound complications after cesarean delivery with Pfannenstiel incision: A randomized clinical trial

Abstract: The rate of wound complications, including superficial wound separation, did not differ according to the subcutaneous closure in cesarean delivery with Pfannenstiel incision. It is not possible to predict wound complications using previously defined clinical and operative risk factors, including subcutaneous tissue thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“… 4 Two additional RCTs and a meta-analysis since supports re-approximating this tissue layer as previously recommended. 75 77 …”
Section: Standardized Cesarean Delivery Surgical Techniquementioning
confidence: 99%
“… 4 Two additional RCTs and a meta-analysis since supports re-approximating this tissue layer as previously recommended. 75 77 …”
Section: Standardized Cesarean Delivery Surgical Techniquementioning
confidence: 99%
“…Seroma is the accumulation of inflammatory exudate in the tissue due to surgical trauma [11]. The incidence of noninfectious surgical site complications such as seroma and hematoma after cesarean section ranges between 3% and 30%, which may result in wound dehiscence and surgical site infection [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of cesarean section, one of the most common surgical procedures [1], has increased significantly in the last two decades, especially in developed countries [2]. After surgical procedures, wound complications develop in 3 to 30% of the patients [3]. There are 2 types of surgical site complications: Infectious and non-infectious (seroma, hematoma, wound dehiscence) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the outcomes were not changed in the case of individual study exclusion. Furthermore, when we excluded the quasi-RCTs from the present analysis we observed that the significant effect of wound closure on aggregated wound disruption was not affected (1979 women, REM, OR 0.53, 95% CI 0.33-0.84, outcomes from eight studies 21,22,[24][25][26][27][28]30 ).The remaining indices were not analysed in the included quasi-RCTs; hence no sensitivity analysis was needed.…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…[21][22][23][24][25][26][27][28][29][30] Of them, 1849 underwent subcutaneous tissue closure through running or interrupted sutures, whereas in the remaining 1847 women the subcutaneous tissue was not closed. Corbacioglu et al 21 presented their outcomes according to two separated follow-up examination intervals, evaluating the women in the first and fourth postoperative weeks [Esmer (1) and Esmer (2)]. One study was identified as a quasi-RCT because researchers randomised women based on an alternating-month basis.…”
Section: Included Studiesmentioning
confidence: 99%